'Door‐to‐door': An emerging transnational business model along the Global North‐Global South migration corridor. Issue 1 (21st August 2022) - Kandilige, Leander; Ampah, Geraldine A.
Abstract: The transnational focus in migration studies since the turn of the 20th century has discussed migrants and their migration activities as spanning both origin and destination countries. Migrants' lives and their activities in both origin and destination countries have also been discussed in‐depth in several studies. However, businesses that facilitate in‐kind transnational links migrants maintain with their relatives and friends back home have received far less attention in the literature. This paper bridges this gap by focusing extensively on 'door‐to‐door' a transnational business model that makes in‐kind remittance transfers possible for migrants and their friends and relatives. This exploratory paper discusses the origins, structure, and operations of these businesses in Ghana and in the United Kingdom and the benefits as well as challenges they encounter within the transnational space. We do this by drawing on interviews conducted with Ghanaian migrant‐owned shipping businesses in the United Kingdom and their partners in Ghana.